Update on Poly ADP-Ribose Polymerase Inhibitors in Ovarian Cancer With Non-BRCA Mutations - Xu, Qin; Li, Zhengyu (Frontiers in Pharmacology, 2021)
Poly ADP-ribose polymerase inhibitor (PARPi) has become an important maintenance therapy for ovarian cancer after surgery and cytotoxic chemotherapy, which has changed the disease management model of ovarian cancer, greatly decreased the risk of recurrence, and made the prognosis of ovarian cancer better to certain extent. The three PARPis currently approved by the United States Food and Drug Administration (FDA) and the European Medicines Agency (EMA) for the treatment of ovarian cancer are Olaparib, Niraparib and Rucaparib. With the incremental results from new clinical trials, the applicable population of PARPi for ovarian cancer have expanded to population with non-BRCA mutations. Although BRCA mutated population are still the main beneficiaries of PARPi, recent clinical trials indicated PARPis’ therapeutic potential in non-BRCA mutated population, especially in homologous recombination repair deficiency (HRD) positive population. However, lack of unified HRD status detection method poses a challenge for the accurate selection of PARPi beneficiaries. The reversal of homologous recombination (HR) function during the treatment will not only cause resistance to PARPis, but also reduce the accuracy of the current method to determine HRD status. Therefore, the development of reliable HRD status detection methods to determine the beneficiary population, as well as rational combination treatment are warranted. This review mainly summarizes the latest clinical trial results and combination treatment of PARPis in ovarian cancer with non-BRCA mutations, and discusses the application prospects, including optimizing combination therapy against drug resistance, developing unified and accurate HRD status detection methods for patient selection and stratification. This review further poses an interesting topic: the efficacy and safety in patients retreated with PARPis after previous PARPi treatment---“PARPi after PARPi”.